Comparing the risk of falls between rural and urban elderly - Guilherme Tavares de Arruda; Cyntia Scher Strelow; Áureo Júnior Weschenfelder; Michele Adriane Froelich; Hedioneia Maria Foletto Pivetta; Melissa Medeiros Braz (Universidade Estadual de Maringá, 2018)
The aim of this study was to compare the risk of falls and characterize them in the urban and rural elderly. Observational study with elderly from urban and rural areas in the interior of the State of Rio Grande do Sul, evaluated by the Fall Risk Score and further criteria for the evaluation and characterization of the last fall within 12 months. A total of 125 elderly, 89 urban and 36 rural was evaluated. There was a high prevalence of medication use (93.6%), impaired vision (35.2%) and previous falls (81.6%) in the total sample of individuals as well as the risk of falls (76.8%) without differences between the groups. The variables of statistical significance were impaired hearing (p = 0.009) and impairment of the lower limbs (p = 0.04). Both the elderly living in rural areas and in urban areas showed high risk for falls in the group studied, with no significant difference between them. Thus, it is worth highlighting the importance of making a health work for guidance on falls.